The Effect of Distraction Techniques on the Pain of Venipuncture in Children: A Systematic Review - Mohammad Sadegh Rezai; Amir Hossein Goudarzian; Azar Jafari-Koulaee; Masoumeh Bagheri-Nesami (Mazandaran University of Medical Sciences, 2016)
Context Venipuncture has been reported as one of the major sources of pain in the children's wards. Various distraction techniques have been used so far to reduce this pain. Distraction technique is one of the non-pharmacological methods of pain control that uses the five senses in order to focus the patient's attention on other stimuli. Objectives This study aimed to determine the effect of distraction techniques on the pain of venipuncture in children. Data Sources In this systematic review study, all RCTs about distraction techniques were reviewed with no time limit. In order to find evidence in this context, English and Persian scientific databases (PubMed, Elsevier, SID, e.g.) were searched by specified keywords like venipuncture, distraction, and pain. Study Selection All studies assessing the effect of distraction techniques on the pain of venipuncture in children were examined in our systematic review. A number of 148 articles were found in the initial investigation of titles, abstracts, and main-texts. After the elimination of duplicates and irrelevant ones, eventually 31 RCT studies and 2 review articles entered the study. Data Extraction A checklist was used to extract required data from relevant articles on name, year and type of study, sample size, age range of participants, type of intervention, employed method, and obtained results. Results Based on the findings, various techniques of distraction were used on pain control in children including music, virtual reality, audio-visual equipment such as cartoons, animation and video game, squeezing rubber balls, Filippits distraction cards, Hugo point ice massage, making bubbles, breathing exercise, Kaleidoscope color screen and touching the palm of the hand to reduce the pain of venipuncture. Conclusions Distraction techniques can reduce the pain of venipuncture in children. It is suggested to make these techniques more effective and apply them by considering the age and mental and physical conditions of children.